DETERMINAN KEJADIAN BERAT BAYI LAHIR RENDAH (BBLR) DI RSUD KOJA, JAKARTA UTARA - Thresya Febrianti; Nasro Abdullahi Omar; Mizna Sabilla; Rusman Efendi; Arum Ariasih (IAKMI South Tangerang Branch, 2022)
Abstract Background: Globally, it is estimated that 15–20% of all births, or >20 million newborns annually, are low birth weight infants. Low- and middle-income countries account for a disproportionate burden of LBW. Objective: The aim of this study was to determine the associated risk factors of LBW in Koja Hospital Method: This study used a cross-sectional study. The sample consisted of 233 respondents from 4,169 total population of mothers giving birth at the Koja Regional General Hospital in 2019. The dependent variable was LBW and the independent variables were anemia, chronic energy deficiency (CED), maternal age, and pregnancy distance. The sampling technique was systematic random sampling. Data analysis used a Chi-Square Test. Result: The prevalence was 48.1% for LBW. The factors associated with LBW in Koja Hospital were age and CED (p value= 0.009 and 0.001). Anemia and pregnancy spacing was no significant relationship with LBW in Koja Hospital (p value=0.308 and 0.544). Conclusion: There was a significant relationship between CED and the age of maternal and LBW in Koja Hospital. Mothers who experience CED during pregnancy can improve and maintain nutritional intake and increase the amount of consumption, especially to consume of energy-containing foods. Keywords: LBW, age of maternal, chronic energy deficiency, anemia.